Factors Influencing Maternal Readiness for Hospital Discharge from Dual Perspectives of Couples - Wenjing Xia; Yan Shi (Clinical and Experimental Obstetrics & Gynecology)
Background: Assessment of maternal readiness for discharge is critical. Higher level of discharge readiness can significantly improve maternal and family members’ depression and anxiety, and reduce the incidence of puerperal complications and neonatal diseases. Understanding how couples navigate and negotiate the challenges and demands of readiness for discharge after delivery has important implications for family health. This study aimed to investigate maternal readiness for hospital discharge and analyze the influencing factors under the dualistic perspective of the couple. Methods: A prospective questionnaire study was administered to 374 women using Maternal and spousal general information questionnaire, Maternal Readiness for Discharge Assessment Scale, and Relationship Satisfaction Scale. Results: Maternal readiness for hospital discharge was assessed with an average score of 177.17 ± 18.67. The total score of the Relationship Satisfaction Scale was 37.83 ± 1.90, and the total score of the spousal Relationship Satisfaction Scale was 36.25 ± 2.18. The results of the hierarchical linear regression equation modeling showed that maternal relationship satisfaction independently explained 8.9% of the total variance in readiness for discharge after controlling for the effects of maternal and spousal general information (p < 0.001), and spousal relationship satisfaction independently explained 10.3% of the total variance in readiness for discharge after controlling for the effects of maternal and spousal general information and maternal relationship satisfaction (p < 0.001). Conclusions: Higher levels of relationship satisfaction were associated with higher maternal readiness for discharge. The important predictive role played by couple intimacy satisfaction in readiness for discharge should be emphasized.